LITERASI DIGITAL SISWA KELAS IV MELALUI PENGGUNAAN SCRATCH DALAM PEMBELAJARAN IPAS DI SD NEGERI 185 PALEMBANG - Ilda Rezki Putri Pratiwi Ritonga; Yasir Arafat; Murjainah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the digital literacy of fourth-grade students through the use of Scratch in IPAS learning on the topic “Me and My Needs” at SD Negeri 185 Palembang. This study employed a qualitative descriptive method with data collection techniques including observation, interviews, questionnaires, and documentation. The results showed that the use of Scratch supported the development of students’ digital literacy, as indicated by increased activeness, understanding, and student engagement in the learning process, although the use of devices was carried out alternately. The observation results indicated that students’ digital literacy was categorized as very good, while the questionnaire results showed that most students were in the very good category with a percentage of 84,57%. Although there were still limitations in facilities and the need for guidance in using technology, Scratch was considered effective in supporting the digital literacy of elementary school students.